Belief, confidence, and motivation to use the paretic upper limb in daily life over the first 24 weeks after stroke - Waddell, Kimberly J. (J Neurol Phys Ther, 2019)
BACKGROUND AND PURPOSE: The recovery patterns of upper limb (UL) impairment after stroke are established. Psychosocial factors such as belief that paretic UL recovery is possible, confidence, and motivation to use the paretic UL in everyday tasks are unexplored early after stroke. The purpose of this exploratory study was to characterize belief, confidence, and motivation to use the paretic UL in daily life, and self-perceived barriers to UL recovery over the first 24 weeks post-stroke. METHODS: This was a longitudinal cohort study (n=30) with eight assessment sessions over the first 24 weeks post-stroke. Belief, confidence, and motivation to use the paretic UL and self-perceived barriers were quantified via survey and analyzed using descriptive statistics. Change in the number of self-perceived barriers between weeks 2 and 24 was tested using a paired samples t-test. The relationship between UL capacity, depressive symptomatology, cognition and each psychosocial factor were examined using Spearman’s rank-order correlation analyses. RESULTS: Twenty-two participants completed all study assessments. Belief, confidence, and motivation were high across the 24 weeks, with little variation. There was no difference between the average number of barriers from weeks 2 to 24. There was no relationship between the clinical measures and psychosocial factors at week 2, 12, or 24. DISCUSSION AND CONCLUSIONS: High levels of belief, confidence, and motivation appear consistent over the first 6 months post stroke. The lack of correlations between psychosocial factors and clinical measures suggests belief, confidence, and motivation may not be vulnerable to functional status early after stroke. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1)